Characterizing Intercellular Communication of Pan-Cancer Reveals SPP1+ Tumor-Associated Macrophage Expanded in Hypoxia and Promoting Cancer Malignancy Through Single-Cell RNA-Seq Data - Wei, Jinfen; Chen, Zixi; Hu, Meiling; He, Ziqing; Jiang, Dawei; Long, Jie; Du, Hongli (Frontiers in Cell and Developmental Biology, 2021)
Hypoxia is a characteristic of tumor microenvironment (TME) and is a major contributor to tumor progression. Yet, the subtypes identification of tumor associated non-malignant cells at single-cell resolution, and how they influence cancer progression under hypoxia TME remains largely unexplored. Here, we used RNA-seq data of 424,194 single cells from 108 patients to identify the subtypes of cancer cells, stromal cells, and immune cells as well as evaluate their hypoxia score, and also to uncover potential interaction signals between these cells in vivo across six cancer types. We identified SPP1+ tumor-associated macrophages (TAMs) subpopulation potentially enhanced epithelial-mesenchymal transition (EMT) by interaction with cancer cells through paracrine pattern. We prioritized SPP1 as a TAMs-secreted factor to act on cancer cells and found a significant enhanced migration phenotype and invasion ability in A549 lung cancer cells induced by recombinant protein SPP1. Besides, prognostic analysis indicated higher expression of SPP1 was found to be related to worse clinical outcome in six cancer types. SPP1 expression was higher in hypoxia score-high macrophages based on single cell data, which was further validated by in vitro experiment that SPP1 was upregulated in macrophages under hypoxia-cultured compared with normoxic condition. Additionally, differential analysis demonstrated that hypoxia potentially influence extracellular matrix remodeling, glycolysis and interleukin-10 signal activation in various cancer types. Our work illuminates the clearer underlying mechanism in the intricate interaction between different cell subtypes within hypoxia TME and proposes the guidelines for the development of therapeutic targets specifically for patients with high proportion of SPP1+TAMs in hypoxic lesions.